ANALISIS KINEMATIKA GERAKAN SPIKE MENGGUNAKAN SOFTWARE KINOVEA PADA ATLET BOLA VOLI KOPI LOTONG CLUB - Asrul; Yuni Alfyanti , Aryanindya; Hamka, Ramdan; Ramadan, Afif; Sakimufli; Aldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Spike is one of the primary attacking techniques in volleyball that requires proper movement coordination to produce effective attacks. This study aimed to analyze the kinematic characteristics of the spike movement using Kinovea software in Kopi Lotong Club volleyball athletes. This study employed a quantitative approach with a descriptive method. The subjects consisted of three volleyball athletes selected using purposive sampling. Data were collected by recording each athlete performing one spike and then analyzed using Kinovea software. The measured parameters included vertical jump height and ball contact height. The results showed that Athlete A1 achieved a vertical jump height of 65.93 cm and a ball contact height of 277.20 cm, Athlete A2 achieved 52.11 cm and 250.14 cm, while Athlete A3 achieved 61.00 cm and 259.82 cm, respectively. The average vertical jump height was 59.68 cm, whereas the average ball contact height was 262.39 cm. The findings indicate that Kinovea provides objective movement measurements and can be used as an effective tool for evaluating spike techniques in volleyball athlete training.